Spatial, temporal and demographic distribution characteristics of adenomyosis symptom clusters from the perspective of traditional Chinese medicine: a multicenter cross-sectional study in China from 2020 to 2022 - Wang, Xin; Tao, Yu; Fu, YuDan; Yang, XinChun; Zhao, RuiHua (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to explore the differences in symptom clusters of adenomyosis (AM) patients across spatial, temporal, and age-stratified dimensions based on the theory of “Treatment in Accordance with Three Categories of Etiologic Factors”.MethodsA cross-sectional study was conducted in China from 2020 to 2022, involving 1,816 AM patients. Univariate analysis, symptom co-occurrence matrices, and hierarchical clustering were used to compare clinical and symptom cluster characteristics across different latitudes (low latitude area: 691 cases vs. high latitude area: 1,125 cases), seasons (warm: 652 cases vs. cold: 473 cases), and age groups (<40 years: 895 cases vs. ≥s. years: 921 cases).ResultsAM symptom clusters exhibited significant geographical, seasonal, and age-related variations, with “Blood Stasis Syndrome” as the core pathological mechanism. In the spatial dimension, the high latitude region exhibited a “syndrome of Cold Coagulation” characterized by cold intolerance (co-occurrence frequency: 3,973), treated by warming Yang and dispersing cold. The low latitude region displayed a “Spleen-Qi Deficiency and Blood Stasis” marked by fatigue (co-occurrence frequency: 2,492), treated by invigorating the spleen and supplementing Qi. In the temporal dimension, during cold seasons, cold intolerance (co-occurrence frequency: 2,029) reinforced the “Cold Coagulation”, treated by warming Yang and dispersing cold. In warm seasons, sweating had the highest co-occurrence frequency (2,054), suggesting a “Dampness” component, treated by invigorating the spleen to resolve dampness. In the age dimension, younger patients exhibited a “Cold Coagulation and Blood Stasis with Liver Qi Stagnation” with cold intolerance as the core symptom (co-occurrence frequency: 3,171), accompanied by irritability (39.66%) and premenstrual or menstrual irritability (34.30%), treated by warming Yang, dispersing cold, and soothing the liver to regulate Qi. Elder patients displayed a “Qi Deficiency and Blood Stasis” pattern with fatigue as the core symptom (co-occurrence frequency: 2,121), accompanied by menorrhagia (40.28%), treated by supplementing Qi and nourishing blood.ConclusionIntegrating TCM theory with data mining techniques, this study established a “time-space-human” three-dimensional syndrome differentiation model for AM, providing a critical framework for advancing precision medicine in TCM gynecology.